1999 Philippine Talent Search for Young Scientists (PTSYS) award - Vallar, Edgar A. (Animo Repository, 1999)
Dr. Edgar Vallar of the Chemistry Department, placed second in the 1999 Philippine Talent Search for Young Scientists (PTSYS) Award among 16 qualified candidates from all over the country. Vallar presented his research titled Generation of 589 nm Laser Radiation by Sum-Frequency of the 1319 nm Output of a Single Nd:YAG Laser (II) to a NAST panel in March, 1999.